The politics of liberation heritage in postcolonial southern Africa, with special reference to Mozambique - Jopela, Albino Pereira de Jesus (My University, 2017)
This study analyses the politics of liberation heritage in postcolonial southern Africa with special reference to Mozambique. The aim is to scrutinise the different ways in which liberation heritage discourse is used and mobilised to construct a range of socioeconomic and political values in the southern African region and to examine the processes of heritagization in Mozambique based on field observations at two national heritage sites: Chilembene and Matchedje. I adopt the conceptualisation of heritage as discourse and put the hegemonic Western heritage discourses into historical perspective in order to explore how this Western understanding of the past has influenced the official discourse and practice in southern Africa in both colonial and postcolonial periods. I argue that the process of re-appropriation and ‘mimicry’ which allow the perpetuation of Western paradigms in the conception of heritage result from a combination of geopolitical and socio-economic contexts and circumstances at play nationally, regionally and globally, combined with the strategies adopted by former national liberation movement’s ruling elites to pursue their own nationalist agendas related to state-crafting and nation-building. I also argue that the recent traction that has led to the institutionalisation of liberation heritage discourse in southern Africa, represents a specific way in which former national liberation movements, now in government, have tried to respond to changes in circumstances marked by an increasing contestation by the different social groups over the content of the official discourse of ‘the past’, based on selective memories of the liberation struggle, in an increasingly disputed multi-party democratic dispensation. To understand the politics of heritagization of the liberation struggle in postcolonial Mozambique, I look at FRELIMO’s efforts to undertake selective celebrations and to silence particular ‘pasts’ for particular ‘presents’ during the struggle years as well as through the different socio-political and economic contexts of the successive presidencies: Samora Machel (1975-86), Joaquim Chissano (-2004) and Armando Guebuza (-2014). By (1) addressing the question of why and how the heritagization of this particular category of the past (i.e. liberation heritage) accomplishes the reproduction of state power held by ruling elites of former national liberation movements, and by (2) illustrating the networks of meanings and practices on which liberation heritage rests, and by (3) analysing the socioeconomic, cultural and political work it does, this study contributes to the embryonic body of knowledge about heritage processes in southern Africa.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2017.
Keywords: Historical sites--Mozambique; Cultural property--Mozambique; Postcolonialism--Africa, Southern; Politics--Africa, Southern; Economics--Sociological aspects